Prognostic factors and outcomes for osteosarcoma: An international collaboration - (:unkn) unknown (ELSEVIER SCI LTD, 2009)
We aimed to evaluate the prognostic significance of traditional clinical predictors in osteosarcoma through an international collaboration of 10 teams of investigators (2680 patients) who participated. In multivariate models the mortality risk increased with older age, presence of metastatic disease at diagnosis, development of local recurrence when the patient was first seen, use of amputation instead of limb salvage/wide resection, employment of unusual treatments, use of chemotherapeutic regimens other than anthracycline and platinum and use of methotrexate. it was also influenced by the site of the tumour. The risk of metastasis increased when metastatic disease was present at the time the patient was first seen and also increased with use of amputation or unusual treatment combinations or chemotherapy regimens not including anthracycline and platinum. Local recurrence risk was higher in older patients, in those who had local recurrence when first seen and when no anthracycline and platinum were used in chemotherapy. Results were similar when limited to patients seen after 1990 and treated with surgery plus combination chemotherapy. This large-scale international collaboration identifies strong predictors of major clinical outcomes in osteosarcoma. (C) 2009 Published by Elsevier Ltd.
Keywords: Osteosarcoma; Clinical predictors; Prognosis; Survival; Metastasis; International collaboration; HIGH-DOSE METHOTREXATE; NONMETASTATIC OSTEOSARCOMA; ADJUVANT CHEMOTHERAPY; MURAMYL TRIPEPTIDE; OSTEOGENIC-SARCOMA; RANDOMIZED-TRIAL; ONCOLOGY-GROUP; LIMB-SALVAGE; SURVIVAL; INTERGROUP